A novel family of optically transparent fluorinated hyperbranched polyimides with long linear backbones and bulky substituents. (15th February 2020) - Liu, Yu; Guo, Jinyu; Wang, Jiuyang; Zhu, Xiaoyu; Qi, Duo; Li, Wenze; Shen, Kunzhi
Graphical abstract: A series of novel FHPIs (namely FHPI Ⅰ−Ⅳ) with a long chain structure and numerous bulky phenyl substituent groups were successfully synthesized. These new FHPIs have excellent solubility, desirable film−forming property and properties great thermal stability. Meanwhile, they also exhibit excellent optical properties, such as light color, extremely high optical transmittance, very low birefringence, adjustable refractive indices at 650 nm, and extremely low absorption loss in near−infrared region, especially at the communication wavelengths. All of the obtained characterization data demonstrates that the new FHPIs synthesized herein have excellent potential for use in optical devices. Highlights: A series of low colored and transparent fluorinated hyperbranched polyimides were synthesized; Each of these polymers exhibits a long linear segment and bulky pendant groups; These novel FHPIs exhibit excellent film–forming properties and good optical properties. Abstract: We demonstrated here for the first time the synthesis of fluorinated hyperbranched polyimide (FHPIs) and an evaluation of their properties. A series of novel fluorinated hyperbranched polyimides were respectively synthesized via a two–step chemical imidization method involving a polycondensation reaction between 1, 3, 5–tris(2–trifluoromethyl–4–aminophenoxy) benzene (TFAPOB) and four different dianhydride monomers bearing bulky substituents. The properties of the synthesized FHPIs (individually denoted as FHPI I–IV) were characterized by Fourier-transform infrared, nuclear magnetic resonance (NMR), Near-IR, and UV-vis spectroscopy, techniques as well as via, atomic force microscopy (AFM), tensile testing, dielectric constants, differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA), In addition, the dielectric constants, chromaticity values, refractive indices, and birefringence values of these materials were determined. The obtained FHPIs showed good solubility and film–forming properties. The FHPIs exhibited excellent optical properties which included very light color, outstanding optical transparency (80–85% at 450 nm, 86–88% at 550 nm, 88–89% at 800 nm), birefringence values ranging from 0.0011 to 0.0020, adjustable refractive indices (1.4721–1.5644 at 650 nm), a cut–off wavelength within 353 nm, and a low absorption range in the near–infrared region. These materials would be ideal candidates for use in optical devices.